Design of PIFA MIMO antenna with parasitic effect for future 5G wireless applications / Bazilah Baharom ... [e al.] - Baharom, Bazilah; Ali, M.T; Awang, Robi'atun Adayiah; Jaafar, Hajar; Yon, Hamizan (Universiti Teknologi MARA, 2019)
In recent technologies, MIMO systems become one of the promising technology used in wireless applications. Therefore, the demand for integration of using multiple antennas in user applications has enhanced. When involving MIMO system, the mutual coupling among the antennas must be low as possible in order for the antenna to give optimum performance. This paper presents two design configurations of compact two-element PIFA MIMO working at 15 GHz for future 5G wireless applications. The operating frequency met the requirement to work in future 5G environment. Both are designed with the total size of. In this paper, a study on technique adding parasitic element to the PIFA MIMO was investigated. The technique proposed is to improve gain as well as improve isolation due to mutual coupling between the antennas. The simulated and measured results show the satisfactory performance of PIFA MIMO antenna, with gain from 6 dB to 8 dB and mutual coupling reduced to around -27 dB at the resonant frequency.